2001
DOI: 10.1111/j.1469-185x.2000.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources and bioavailability of phosphorus fractions in freshwaters: a British perspective

Abstract: This paper seeks a perspective on the forms of phosphorus which promote aquatic eutrophication, with the particular quest of establishing their sources. A short background traces the development of understanding of nutrient enrichment and the suppositions about the relative contributions of agriculture, sewage and detergent residues. Most aquatic systems, and their primary producers, are naturally deficient in biologically-available phosphorus. Aquatic plants have evolved very efficient phosphorus uptake mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 93 publications
1
95
0
1
Order By: Relevance
“…These nutrients limit primary production especially in freshwater ecosystems [50,51]. Bioavailability of these nutrients in aquatic ecosystems varies among living organisms which mostly comprises of dissociated orthophosphate ions (H 2 PO 4 -, HPO 4 2-and PO 4 3-) in the case of P [52] and nitrite (NO 2 -), nitrate (NO 3 -) and ammonium (NH 4 + ) ions in the case of N [24]. Bottom-up control by phytoplankton also equally influences N and P, indicating co-limitation in aquatic ecosystems [53].…”
Section: Resultsmentioning
confidence: 99%
“…These nutrients limit primary production especially in freshwater ecosystems [50,51]. Bioavailability of these nutrients in aquatic ecosystems varies among living organisms which mostly comprises of dissociated orthophosphate ions (H 2 PO 4 -, HPO 4 2-and PO 4 3-) in the case of P [52] and nitrite (NO 2 -), nitrate (NO 3 -) and ammonium (NH 4 + ) ions in the case of N [24]. Bottom-up control by phytoplankton also equally influences N and P, indicating co-limitation in aquatic ecosystems [53].…”
Section: Resultsmentioning
confidence: 99%
“…This high PP concentration in Lake Victoria will result in high P sedimentation and consequent P enrichment of the bottom sediments (Hecky 1993). The sedimented phosphorus may be permanently buried or may undergo biological and chemical transformation to the bio-available SRP which is recycled back into the water column (Reynolds and Davies 2001) and allowing lake sediments to act as an internal source of P and to potentially sustain P concentrations in overlying waters.…”
Section: Discussionmentioning
confidence: 99%
“…These might include the amount of aluminum, iron, and calcium in lake sediments; dominance of the zooplankton community by efficient grazers like Daphnia, which can increase the downward flux of phosphorus-containing particulate matter incorporated in fecal pellets; the form in which phosphorus is supplied (i.e., inorganic or organic, dissolved or particulate), which determines if it will be readily incorporated into the biologic cycle of lakes or settle to the sediments; sediment resuspension in shallow, wind-exposed lakes; and bioturbation of material likely to have passed through benthic animals or fish, which creates a ''gluing'' of the particles into larger flocs (Reynolds and Davies 2001;Brett et al 2005aBrett et al , 2005bCarpenter 2005;Jensen et al 2006;Brett and Benjamin 2008). Moreover, Nu¨rnberg and LaZerte (2004) indicated that the ratio of watershed-to-lake area can be an important predictor in lakes with complex morphology, while further improvements may be obtained by explicitly considering surrogate variables of soil geochemistry (humic and fulvic acids) such as DOC or lake water color (Nu¨rnberg and Shaw 1998).…”
Section: Model-prediction Error and Suggestions For Progressmentioning
confidence: 99%